The Effect of Information Literacy on Maize Production: Case study of small-scale farmers in Inonge Village, Kazungula District of Zambia - Kanyamuna, Vincent; Mulele, Sylvia Chitola; Kanyamuna, Chuma Sylvin; Kanyamuna, Lubomba Mudenda; Musanda, Paul (Advances in Social Sciences Research Journal, 2021)
The study aimed at exploring the impact of information literacy on maize production and focused on a case study of small-scale farmers in Inonge village of Kanzungula District in Southern Province, Zambia. Besides the review of relevant literature, the study conducted a questionnaire-based case study on 20 small-scale farmers and conducted an in-depth interview with one agriculturalist from the Ministry of Agriculture. The analysis of the study showed that farmers need information for various purposes to enhance their agricultural activities, and they use different sources and media to access such information. Many of the farmers, however, are not well aware of modern techniques of agriculture and they seldom use such techniques for farming. Due to some problems such as high rate of illiteracy, inadequate contact with agricultural extension officers, language barrier and bad television and radio reception, farmers are not satisfied in getting agricultural information. The paper concludes that information literacy has an effect on maize production and certain recommendations for policy, practice and further research have been provided for the improvement of information literacy of the farmers in Inonge village. These include government to reconsider public agricultural policy reforms on one hand and for the local communities and their leaderships to reorganize themselves and tackle the information challenges facing them on the other. More focused research was still needed to understand and contextualize Inonge village agricultural challenges and prospects.